THE ROLE OF DYNAMIC SYSTEMS IN MOTOR DEVELOPMENT RESEARCH: JUST A METAPHOR OR A NOTABLE REALITY? - Ivan Šerbetar (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
In the present article an application of a new theory of motor control in the context of motor development theories and research has been discussed. In a brief overview of traditional theories of motor development a neuro-maturational theory is mentioned along with the two prominent proponents − McGraw & Gesell. Bernstein's fundamental insights in motor control were emphasized, such as the concepts of degrees of freedom and synergies, along with his contribution to the measurement technology and quantification. Basic principles of dynamic systems theory and common concepts such as self-organization, patterns, attractors or non-equilibrium systems are briefly described. In the main part, an example of research in motor development carried out in dynamical perspective was introduced. The chosen example was the body of the research performed by Thelen et al. (1982, 1984, 1990) on a newborn's stepping. The distinction between the maturational perspective in which all the sequences of motor development are the result of maturation of nervous system, and the dynamic perspective in which development is seen as a mutual interaction between a number of body systems, including neural and muscular systems, which continuously affect the movement although none of them dominate (Kamm et al., 1990) has been made.